2001
DOI: 10.1097/00006254-200111000-00004
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial of Care for Women With Preterm Labour: Home Management Versus Hospital Management

Abstract: This article has been peer reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…Our results are in line with previous studies done before the widespread use of ultrasound in which long-term hospitalization (between 6 and 16 days) was demonstrated to be of no use in prolonging pregnancy compared to outpatient management [25,26]. Moreover, they are consistent with other nonrandomized reports in which clinical protocols incorporating ultrasound assessment of CL were shown to be useful in avoiding unnecessary prolonged hospitalization and in reducing the mean hospital stay by about 2 days [17,18,20].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are in line with previous studies done before the widespread use of ultrasound in which long-term hospitalization (between 6 and 16 days) was demonstrated to be of no use in prolonging pregnancy compared to outpatient management [25,26]. Moreover, they are consistent with other nonrandomized reports in which clinical protocols incorporating ultrasound assessment of CL were shown to be useful in avoiding unnecessary prolonged hospitalization and in reducing the mean hospital stay by about 2 days [17,18,20].…”
Section: Discussionsupporting
confidence: 92%
“…The study was designed in the late nineties, well before the extended use of CL in clinical practice. However, although the information obtained in this study may seem to be outdated, there are few studies on women hospitalized because of threatened preterm labor [5,17,18,25,26]. Moreover, recent studies using CL in patients admitted because of threatened preterm labor have shown that the mean CL at admission is comparable with ours and that up to 70-85% of patients admitted will finally deliver at term [4,5,9,13,14].…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Other studies have shown the ineffectiveness of prolonged prophylactic hospitalization in the management of twin gestations prior to the onset of complications. 22,23,24 In summary, the current study reveals that SQT usage in the home for patients at risk for early delivery offers a significant advantage when compared to prolonged hospitalization for tocolytic therapy. Because of the increased gestational age at delivery and fewer low birth weight infants, there were significantly lower costs associated with the care of these women compared to those managed in the hospital.…”
Section: Significancementioning
confidence: 77%
“…This review of home visits included ten RCTs (n = 9274 women); [479][480][481][482][483][484][485][486][487][488] two RCTs were added to the primary studies identified in an earlier review. 489 Further details of the review and the two additional RCTs can be found in Appendix 6, Table 126.…”
Section: Home Visitsmentioning
confidence: 99%